2010
DOI: 10.1590/s1519-69842010000100015
|View full text |Cite
|
Sign up to set email alerts
|

Group size and composition of Guiana dolphins (Sotalia guianensis) (Van Bénèden, 1864) in the Paranaguá Estuarine Complex, Brazil

Abstract: The aim of the present study was to describe the characteristics of Guiana dolphins (S. guianensis) group size and composition in the Paranaguá Estuarine Complex (25° 15' -25° 36' S and 48° 02'-48° 45' W), Paraná State, as well as to verify the existence of relationships between a given environmental variable (water depth, salinity, transparency and temperature) and group size. An area of around 124 km 2 was surveyed by boat from April 2006 to February 2008 in the following subsets of the estuary: Canal do Sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In the South of Brazil, Filla & Monteiro-Filho (2009) found an average group size of 2.13ind/km² and 2.9ind/km² in the Guaratuba and Paranaguá Bays (state of Paraná), respectively. Also in the Paranaguá Bay, Santos et al (2010) registered group sizes ranging from two to 90 individuals. In the Baía Norte (state of Santa Catarina) the average size found was much larger: 29ind/km² (Daura-Jorge et al 2005).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the South of Brazil, Filla & Monteiro-Filho (2009) found an average group size of 2.13ind/km² and 2.9ind/km² in the Guaratuba and Paranaguá Bays (state of Paraná), respectively. Also in the Paranaguá Bay, Santos et al (2010) registered group sizes ranging from two to 90 individuals. In the Baía Norte (state of Santa Catarina) the average size found was much larger: 29ind/km² (Daura-Jorge et al 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Similar results were also found in Paraty Bay (Lodi & Hetzel 1998, Lodi 2003. Santos et al (2010) report that the largest groups of S. guianensis in the protected areas of Paranaguá Estuarine Complex (state of Paraná) occurred due to the local topography, lower predation risk, seasonal distribution and prey abundance. The seasonal variance may be related to changes in the abundance and distribution of the prey, which appears to be strongly influenced by the seasons (Lodi 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Sea turtles are frequently captured in gillnets, especially nets with larger mesh size that have drifted for more than 8 h in the water (Guebert et al 2005). The estuary is considered a nursery ground for fish species (Barletta et al 2008(Barletta et al , 2010 and is an important feeding and resting site for estuarine dolphins and Franciscana (Sotalia guianensis, Pontoporia blainvillei; Santos et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Other populations of this species throughout its distribution have been found to include large numbers of groups containing calves. In the Paranaguá estuarine complex (Paraná State), SANTOS et al (2010) reported that 86.4% of all observed groups of Guiana dolphins contained offspring. In Sepetiba Bay, a region adjacent to Ilha Grande Bay where large aggregations of individuals have been observed, NERY et al (2010) reported that 80.3% of all groups observed contained offspring.…”
Section: Offspring Carementioning
confidence: 99%